2020
DOI: 10.26803/ijlter.19.3.12
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Discovery Learning Module on Geometry for Improving Students’ Mathematical Reasoning Skills, Communication and Self-Confidence

Abstract: The aim of the study was to examine the effectiveness of the Discovery Learning Module on Geometry (D-Geometry Module) in improving reasoning skills, communication, and self-confidence in mathematics among secondary school students. The research design was a quasi-experimental with a non-equivalent control group with pre-test and post-test design, where 128 students were grouped according to gender and the group of the intervention as well as a traditional group. Mathematical reasoning skills, communication, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
0
13
0
1
Order By: Relevance
“…The needs of students facing the 4 th Industrial Revolution (4.0 IR) and the 21 st century require skills in (l) leadership and responsibility (Siregar et al, 2020;Urban & Favlo, 2016). Furthermore, in the 21 st century, ICT advancement is one factor promoted by integrating science, technology, engineering, and mathematics (STEM) education in schools.…”
Section: Introductionmentioning
confidence: 99%
“…The needs of students facing the 4 th Industrial Revolution (4.0 IR) and the 21 st century require skills in (l) leadership and responsibility (Siregar et al, 2020;Urban & Favlo, 2016). Furthermore, in the 21 st century, ICT advancement is one factor promoted by integrating science, technology, engineering, and mathematics (STEM) education in schools.…”
Section: Introductionmentioning
confidence: 99%
“…The learning process is designed to be more meaningful for children. Because learning is done according to the child's development (Bakker, 2018;Fadlilah et al, 2020;Ilhan & Ekber Gülersoy, 2019;Roza et al, 2018;Siregar et al, 2020). The novelty offered to overcome the problems in the research is the development of a character education-based discovery learning model.…”
Section: Introductionmentioning
confidence: 99%
“…Because character education has complete benefits. The advantage of being novelty in the character education-based discovery learning model that is developed is that children are accustomed to scientific thinking, problem solving, and critical thinking (Fadlilah et al, 2020;Ilhan & Ekber Gülersoy, 2019;Roza et al, 2018;Siregar et al, 2020;Winarni et al, 2020). Children are trained to behave positively, especially focusing on the attitude of responsibility and care for primary school education (Djuanda, 2019;Hamriana, 2021;Nugraha, 2020;Safitri, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This result is also in line with the viewpoints of past studies; for example, Bahari (in press) pointed out that cognitive load which can advance or hinder information processed in working memory affects how learners interact with each other in the learning environment. In addition, Siregar et al (2020) proposed that cognitive theory plays an important role in helping students understand self-confidence. For example, McQuaid (2010) confirmed that excessive cognitive load experience can lead to feelings of frustration or failure.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the experience of cognitive overload can lead to feelings of frustration or failure ( McQuaid, 2010 ). Cognitive theory plays an important role in helping students understand self-confidence ( Siregar et al, 2020 ); as a result, poor learning due to cognitive load affects self-confidence. The experience of success in challenging tasks increases students’ self-confidence ( Koumi, 2013 ).…”
Section: Theoretical Framework and Research Hypothesismentioning
confidence: 99%